2006
DOI: 10.1002/ijc.21815
|View full text |Cite
|
Sign up to set email alerts
|

Telomere DNA content and allelic imbalance demonstrate field cancerization in histologically normal tissue adjacent to breast tumors

Abstract: Cancer arises from an accumulation of mutations that promote the selection of cells with progressively malignant phenotypes. Previous studies have shown that genomic instability, a hallmark of cancer cells, is a driving force in this process. In the present study, two markers of genomic instability, telomere DNA content and allelic imbalance, were examined in two independent cohorts of mammary carcinomas. Altered telomeres and unbalanced allelic loci were present in both tumors and surrounding histologically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 59 publications
10
99
0
1
Order By: Relevance
“…Median TC in men with cancer recurrence within 6 years was~50% of TC in men who remained disease-free in tumor (p 5 0.012), and surprisingly, also in tumor adjacent histologically normal tissues (p 5 0.024). As mentioned earlier, the latter supports the concept, shown previously by us and others, 12,15,45 that telomere attrition takes place in histologically normal tissue adjacent to the corresponding tumors, and may thus represent an early event in tumor formation. This phenomenon may reflect ''field cancerization,'' a concept that was introduced to explain the occurrence of genetic alterations in histologically normal tissues adjacent to tumors.…”
Section: Prostate Cancersupporting
confidence: 89%
See 1 more Smart Citation
“…Median TC in men with cancer recurrence within 6 years was~50% of TC in men who remained disease-free in tumor (p 5 0.012), and surprisingly, also in tumor adjacent histologically normal tissues (p 5 0.024). As mentioned earlier, the latter supports the concept, shown previously by us and others, 12,15,45 that telomere attrition takes place in histologically normal tissue adjacent to the corresponding tumors, and may thus represent an early event in tumor formation. This phenomenon may reflect ''field cancerization,'' a concept that was introduced to explain the occurrence of genetic alterations in histologically normal tissues adjacent to tumors.…”
Section: Prostate Cancersupporting
confidence: 89%
“…The latter is in agreement with studies in breast and prostate cancers, which show that telomere attrition takes place in histologically normal tissue adjacent to the corresponding tumors, and thus may represent an early event in the carcinogenic process. 15,45 At the time of their report, the authors hypothesized that telomere alterations may initiate and promote the development of malignancy. 12 In this context, Meeker et al recently observed that telomere length abnormalities represent early and prevalent genetic alterations in the multistep process of malignant transformation in several types of cancer, including breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%
“…33,34 It was reported that telomere length is reduced in histologically normal tissues distant at least 1 cm from the adjacent tumor margins. 35 Although the tissue appears normal, it harbors various genetic changes, including telomere dysfunction, that are reflective of the adjacent carcinogenesis process. This seriously complicates the use of histologically normal tissue as control.…”
Section: Discussionmentioning
confidence: 99%
“…This seriously complicates the use of histologically normal tissue as control. 35,36 Also examining whole tissue sections rather than examining telomere lengths by in-situ methodology, which permits distinction of lesional tissue from contaminating normal tissues is one of the limitations of used methodology. 37 To reduce the challenge of contaminating normal tissues, the paired normal samples in our study were selected with distances more than 1.5 cm to the adjacent tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has previously investigated the nature of field cancerization in both prostate and breast cancers using markers of genomic instability, including telomere DNA content (TC), an established surrogate measure of telomere length and the extent of allelic imbalance (AI) (11,12). These studies have shown telomere alterations and the presence of AI in both tumor and TAHN tissues.…”
Section: Introductionmentioning
confidence: 99%